All in on AI : how smart companies win big with artificial intelligence - Davenport, Thomas H., 1954-; Mittal, Nitin (AI innovator) (Boston : Harvard Business Review Press, 2023)
A fascinating look at the trailblazing companies using artificial intelligence to create new competitive advantage, from the author of the business classic, Competing on Analytics, and the head of Deloitte's US AI practice. Though most organizations are placing modest bets on artificial intelligence, there is a world-class group of companies that are going all-in on the technology and radically transforming their products, processes, strategies, customer relationships, and cultures. Though these organizations represent less than 1 percent of large companies, they are all high performers in their industries. They have better business models, make better decisions, have better relationships with their customers, offer better products and services, and command higher prices. Written by bestselling author Tom Davenport and Deloitte's Nitin Mittal, All-In on AI looks at artificial intelligence at its cutting edge from the viewpoint of established companies like Anthem, Ping An, Airbus, and Capital One. Filled with insights, strategies, and best practices, All-In on AI also provides leaders and their teams with the information they need to help their own companies take AI to the next level. If you're curious about the next phase in the implementation of artificial intelligence within companies, or if you're looking to adopt this powerful technology in a more robust way yourself, All-In on AI will give you a rare inside look at what the leading adopters are doing, while providing you with the tools to put AI at the core of everything you do.
Intro -- Contents -- Introduction -- Ch. 1: What Does It Mean to Be AI Fueled? -- Ch. 2: The Human Side -- Ch. 3: Strategy -- Ch. 4: Technology and Data -- Ch. 5: Capabilities -- Ch. 6: Industry Use Cases -- Ch. 7: Becoming AI Fueled -- Notes -- Index -- Acknowledgments -- About the Authors.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on February 22, 2023).
WorldCat record variable field(s) change: 050, 082
Keywords: Business -- Data processing; Artificial intelligence